The Effects of the Multidisciplinary Team_x000D_ Approach on Blood Transfusion_x000D_ - (:unkn) unknown (My University, 2019)
Objective: The Joint Commission and the American Medical Association-Convened Physician Consortium for Performance Improvement reported that the blood transfusions areamong the top five overused treatments in modern medicine. Optimal management of bloodtransfusion is one of the most important factors that increase patient safety, and specialeducation is increasing all over the world in this regard. In this retrospective cohort study,our goal was to investigate the effects of periodic consensus meetings and training on perioperative blood transfusion by a team of different branches of medicine.Methods: Patients over the age of 18 undergoing cardiac surgery and required blood transfusion were included in this study. The transfusions were calculated cumulatively; the changeconcerning years was determined, as well as side effects and complications associated withtransfusion. Patients’ cardiac reserves, laboratory values, anticoagulant drug use frequency,transfused blood volume, complications and mortality rates were recorded. The types ofsurgery, reexploration rate, length of intensive care and hospital stay were recorded.Results: Patients’ age, BMI, comorbidity ratio and antimicrobial drug use did not differbetween years (p>0.05). The length of intensive care and hospital stay, amount of bleeding,mortality rate did not differ (p> 0.05). Cardiopulmonary Bypass time and Cross Clamp timein 2016, were significantly higher (p<0.05) than in 2014 and 2015. The amount of bloodtransfusion did not differ significantly (p>0.05). Besides, after 2014, an increase was observedin platelet transfusion. The change in Hb, Htc, platelet and INR did not differ significantly inthe pre-postoperative period.Conclusion: Training on the restrictive use of blood products did not have a positive influence on blood transfusion in our study. It has been demonstrated that there are challengesin sufficiently transferring the knowledge to the clinical environment.

Amaç: Birleşik Komisyon ve Amerikan Tabipler Birliği tarafından toplanan Performans İyileştirme Konsorsiyumu, kan transfüzyonlarının_x000D_ modern tıbbın ilk beş aşırı kullanımı arasında olduğunu bildirmiştir. Kan transfüzyonunun optimal yönetimi, hasta güvenliğini artıran en önemli_x000D_ faktörlerden biridir ve bu anlamda tüm dünyada özel eğitimler artmaktadır. Bu geriye dönük kohort çalışmasında amacımız, periyodik konsensus toplantılarının ve perioperatif kan transfüzyonu üzerine yapılan eğitimin, farklı tıp dallarından oluşan bir ekip tarafından araştırılmasıdır._x000D_ Gereç ve Yöntem: Kan transfüzyonu gereksinimi bulunan, kalp cerrahisi geçiren 18 yaş üstü hastalar çalışmaya dahil edildi. Transfüzyonlar_x000D_ kümülatif olarak hesaplandı, yıllara göre değişim, yan etkiler ve transfüzyon ile ilişkili komplikasyonlar belirlendi. Hastaların kardiyak rezervleri, laboratuvar değerleri, antikoagülan ilaç kullanım sıklığı, transfüzyon miktarı, komplikasyonlar ve mortalite oranları kaydedildi. Ameliyat_x000D_ tipleri, revizyon oranı, yoğun bakım süresi ve hastanede kalış süresi kaydedildi._x000D_ Bulgular: Hastaların yaş, VKİ, komorbidite oranı, antimikrobiyal ilaç kullanımı yıllara göre farklılık göstermemiştir (p>0.05). Yoğun bakım_x000D_ ve hastanede kalış süresi, kanama miktarı ve mortalite oranı istatistiksel olarak farklı değildi (p>0.05). 2016 yılında CBP ve CX zamanı, 2014_x000D_ ve 2015’e göre anlamlı olarak daha yüksekti (p<0.05). Kan transfüzyonu miktarı anlamlı olarak farklılık göstermedi (p>0.05). Ayrıca 2014_x000D_ sonrası trombosit transfüzyonunda artış gözlendi. Ameliyat öncesi dönemde Hb, Htc, trombosit ve INR’deki değişiklik anlamlı olarak farklılık_x000D_ göstermedi._x000D_ Sonuç: Çalışmamızda restriktif kan ürünü kullanımı ile ilgili eğitimin kan transfüzyonu üzerinde pozitif bir etkiye sahip olmadığı gösterilmiştir._x000D_ Bilginin klinik ortama yeterince aktarılması konusunda zorluklar olduğu ortaya konulmuştur._x000D_
Multidisipliner Ekip Yaklaşımının Kan Transfüzyonu Üzerine Etkileri